Community-based conservation of crop genetic resources - Haan, Stef de (Burleigh Dodds Science Publishing Limited, 2021)
Maintaining and benefitting from plant genetic diversity are key challenges facing agriculture. Challenges include a narrowing genetic base for many key crops, the loss of landraces and wild varieties with agricultural intensification and urbanisation, and the need to develop the role of existing gene banks from repository of genetic diversity to enablers of the flow of germplasm and genetic information for breeding more robust varieties. Plant genetic resources: A review of current research and future needs surveys the wealth of research addressing these challenges and the opportunity for a more integrated, global approach to protecting and leveraging plant genetic diversity for a more sustainable agriculture. The book assesses ways of valuing and monitoring plant genetic diversity and discusses advances in in-situ and ex-situ strategies for conserving plant genetic diversity. The book concludes by reviewing ways of enhancing the use of plant genetic diversity, including participatory plant breeding programmes and more effective seed systems. With its eminent editor and range of international expertise, Plant genetic resources: A review of current research and future needs will be a standard reference for university and other researchers studying crop genetic resources and breeding, staff managing genebanks and germplasm collections, government and other agencies regulating the collection, storage and exchange of germplasm, as well as companies involved in crop breeding. Color tables, photos and figures.